The Effect of Transformational Leadership Style, Work Motivation, And Organizational Culture on Employee Performance in Village Credit Institutions (LPD) in The Selemadeg District, Tabanan Regency - Ni Putu Linda Ayu Pramesti; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
The success or failure of a business is directly related to its human resources, making them a valuable asset. Therefore, good human resource management is very important for the growth of a company's efficiency and productivity. The purpose of this study is to analyze the relationship between employee performance at LPD in Selemadeg District and leadership style, motivation, and organizational culture that emphasizes change. The Village Credit Institution (LPD) in Selemadeg District, Tabanan Regency, was the location of this investigation. The influence of transformational leadership style, intrinsic motivation at work, and corporate culture on productivity was the focus of this study. The staff of the Village Credit Institution (LPD) in Selemadeg District, Tabanan Regency (n=80) were the population and sample of this study. Due to the small sample size (less than 100), all employees were included as respondents in the multiple linear regression analysis conducted using SPSS version 25 software. The sampling approach used was the saturated sampling method, also known as the census method. The village credit institution (LPD) in Selemadeg District, Tabanan Regency, will see an increase in employee performance as a direct result of a more transformational leadership style, according to this study's analysis of the relationship between transformational leadership, work motivation, and organizational culture.